(untitled) (Scientific journal of the Fergana State University, 2023)
The biological characteristics and chemical composition of the plants Vigna sinensis (beans), Сicer oriyentinum (peas), Phaselous ayreus (mosh), Аrachhis hypogaea (peanuts) grown in Uzbekistan as food products with export potential are characterized.